Standar Kompetensi Guru Profesional - idris (el Hakim Press, 2017)
With today?s learning and educational system, teacher is the first and main component between other components (student, curriculum, the learning subject, learning purposes, teaching methods, means and tools of learning, educational evaluation, and the learning environmental). Therefore, the existence of a professional teacher is much needed in education. A professional teacher is someone that have special skills, educated and trained in the field of teaching with a good performance, that makes him able to conduct his duty and function as teacher with his experience and skills maximally in this field. A professional teacher must have competence standards, such as: (1) pedagogic competence, (2) attitudinal competence, (3) professional competence, and (4) social competence. Those competences have to be nationally standardize, therefore there is certain minimal skills criterion and standards that have to posses and mastered by a teacher, that eventually can give objective evaluations to guarantee and quality control both for the teacher and the educational environment (such as: by giving teacher certification that have rank).